2000
DOI: 10.1080/07315724.2000.10718944
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Healthcare Professionals’ Knowledge About Warfarin-Vitamin K Drug-Nutrient Interactions

Abstract: Although the healthcare professionals surveyed in this study appear to have demonstrated some proficiency in their respective areas of expertise, they exhibited less knowledge in others. Therefore, additional training and integration of knowledge and expertise about drug-nutrient interactions among healthcare professionals are essential to provide appropriate patient counseling and optimal therapeutic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 22 publications
5
41
0
Order By: Relevance
“…Previous studies reported that as there was knowledge gap of the healthcare team with regard to warfarin-nutrient interactions which can lead to disruption in anticoagulant outcomes [8,24,25]. The finding of our study also showed that only 75.6% of the respondents answered correctly on the effect of taking large amount of leafy green vegetables (which are enrich with vitamin K), on warfarin.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…Previous studies reported that as there was knowledge gap of the healthcare team with regard to warfarin-nutrient interactions which can lead to disruption in anticoagulant outcomes [8,24,25]. The finding of our study also showed that only 75.6% of the respondents answered correctly on the effect of taking large amount of leafy green vegetables (which are enrich with vitamin K), on warfarin.…”
Section: Discussionsupporting
confidence: 42%
“…Effective anticoagulation therapy requires systematic and coordinated patient care management by trained anticoagulation therapy providers [12]. Most healthcare providers are confident that they are well skilled in the practical aspects of management [13] but the literature suggests that many undesirable effects of therapy result from inappropriate management rather than patient non-compliance or other aberrations [8,13]. Other study also justified the inadequacy of antimicrobial warfarin interaction knowledge as it showed high incidence of co-prescribing, which carry excess bleeding risk [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aman et al, conducted studies on "Food and Drug Interactions in Pakistan in 2010 " and their results indicated that accurate compliance with medication consumption standards was required [11]. In their study in the United States, Couris Rebecca et al found that the nurses' knowledge of food and drug interactions was not sufficient [12]. In a study entitled "knowledge and awareness of food and drug interactions among health care professionals", Benni et al showed that health care providers (novice physicians and interns) had lower awareness of food and drug interactions [13].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Patients that are prescribed medication with narrow therapeutic range need to be monitored closely for prime care, treatment and for minimising any possible drug-food or drug-drug interactions. So in these circumstances the healthcare professionals play important role.…”
mentioning
confidence: 99%